Vibrational analysis of angle measurement comparator. Issue 7 (October 2016) - Kilikevicius, Arturas; Jurevicius, Mindaugas; Skeivalas, Jonas; Kilikeviciene, Kristina; Turla, Vytautas
Abstract The comparators of angle measurement are designed for measurement of angle gauges (limbs) and angular movements (turning) for calibration measurement errors of measuring systems. The vibration isolation issue for angle comparators is particularly relevant. Vibration analysis became essential for angle comparators operating in dynamic mode and used for precise angular measurements. In this paper, an analysis of wavelet intensity distributions of angle comparators is carried out by applying the theory of covariance functions. Data from measurements of vibrational signals at fixed points were acquired in the form of data arrays (matrices). Estimates of covariance functions between the arrays of data and the estimates of covariance functions of single arrays were calculated upon changing the quantization interval on the time scale. For signal processing, MATLAB 7 software was applied.